The cross-sectional study of Toxoplasma gondii seroprevalence in selected groups of population in Slovakia - Fecková, Miroslava; Antolová, Daniela; Janičko, Martin; Monika, Halánová; Štrkolcová, Gabriela; Goldová, Mária; Weissová, Tatiana; Lukáč, Branislav; Nováková, Mária (Folia microbiologica, 2020)
Toxoplasma gondii is an obligate intracellular protozoan parasite with domestic or free-living members of family Felidae known as the only definitive hosts of the parasite. The study aimed to evaluate the seroprevalence of toxoplasmosis in selected population groups in Slovakia and to analyse the infection risk factors. Totally 1536 serum samples of voluntary respondents were examined by EIA Toxoplasma IgG (Test-Line Ltd., Clinical Diagnostics, Brno, Czech Republic). IgG antibodies to T. gondii were detected in 322 (21.0%) sera, with the highest seropositivity recorded among farmers (42.5%) and hunters (28.5%). According to age, the highest seropositivity was recorded in 12-18-year-old Roma children (46.2%), what confirms increased risk of infection in this minority that often lives in inadequate hygiene conditions. When only adult participants were taken into account, the highest seroprevalence was observed in the age group of ≥ 70 years. Higher risk of infection (p < 0.05) was connected with cat ownership, living in rural residency and consumption of raw meat and meat processing. The results underline the importance of preventive measures and ongoing need to improve the knowledge on toxoplasmosis in both professionals and public.
Keywords: Animals; imunoglobulin G; Toxoplasmosis; průřezové studie; Slovakia; lidé; Toxoplasma; Immunoglobulin G; Risk Factors; séroepidemiologické studie; protilátky protozoální; Cross-Sectional Studies; Antibodies, Protozoan; Seroepidemiologic Studies; rizikové faktory; toxoplazmóza; Slovenská republika; zvířata; Humans